Pelatihan Pencatatan Laporan Keuangan Berbasis Digital Bagi Kelompok Tani Desa Kayu Manis - Twenty Mariza Syafitri; Sri Wulandari; Rike Purnama Sari; Hafiz Nurkholis (Jurnal Dehasen Untuk Negeri, 2023)
The current Digital Era requires people to be able to master and operate technology. This also applies to farmer groups. Farmers Groups are expected to be able to make digital records and bookkeeping to produce accurate financial reports. The benefit of using the "AkuntansiKu" application is that it makes it easier for farmer groups to record financial transactions. The purpose of this Community Service is to assist farmer groups in Kayu Manis Village in recording financial transactions using Digital-based applications that can be obtained on Android or IOS applications. The method used in this Community Service activity begins with an opening from the Community Service Team, presentation of material and discussion about recording digital-based financial reports by demonstrating the various features provided. The results of this Community Service activity are that farmer groups understand basic accounting knowledge, farmer groups can use the "AkuntansiKu" application, and farmer groups can make records of Farmer Business Group financial reports.